Crime, conflict, and peace : violent non-state groups and crop substitution in the Colombia-Ecuador borderland (2017-2021) - Campbell, Mila Pereira (2023)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Relações Internacionais, Programa de Pós-Graduação em Relações Internacionais, 2023.